How to draw : drawing and sketching objects and environments from your imagination - Robertson, Scott, 1966- (Culver City : Design Studio Press, 2013)
With the perspective drawing process concisely communicated by Scott Robertson, this book will be an indispensible addition to the library of anyone interested in learning to draw, as well as those teaching others to draw. Early chapters focus on an introduction to the discipline with later chapters providing the knowledge needed to draw more complex forms and subjects.